Improving students' writing ability of narrative text at the first grade of SMA islam nusantara malang using joint construction - Dewi Ainur Rochma; Yahya Alaydrus; Diah Retno Widowati (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2020)
ABSTRACT : This research aimed to improve students’ writing ability of narrative text at the first grade of SMA Islam Nusantara Malang. Joint construction is a teaching technique that can be used to help teacher in improving students’ writing ability. This study used a classroom action research design. This classroom action research design was conducted in one cycle which consisted of three meetings and last meeting for test. Subject of this study was on the first grade of SMA Islam Nusantara Malang in first grade of IPA with eleven students. Researcher did a pretest to know students’writing ability. Results of students’ score were lower than standard minimum score. Lesson plan was designed as a teaching instruments to reach criteria of success in SMA Islam Nusantara Malang. Criteria of success is 75.00. Besides implementing a joint construction, field notes helped this study to know the process in improving students’ writing ability. Based on result of test and field notes, this study stopped in one cycle because the criteria of success were achieved.In conclusion, joint construction helped the students improve their narrative text writing abilty by 1.) Teacher’s defining narrative text to the class 2.) Putting the student in groups of four 3.) Sharing with students about ways of writing narrative text 4.) Asking the students to have group discussion on narrative text writing 5.) Asking its group to make presentation on narrative text writing 6.) Teacher giving feedback to students’ narrative text writing 7.) Student’s revising their narrative text writing in group. This study suggests that teacher should use steps of joint construction in writing class. The researcher hopes that future researcher can add and complete this study from different research design. Keywords: writing ability, narrative text, and joint Construction.